Patient Satisfaction in Urology: Effects of Hospital Characteristics, Demographic Data and Patients’ Perceptions of Received Care - Schoenfelder, Tonio; Schaal, Tom; Klewer, Joerg; Kugler, Joachim (Urology Journal, 2014)
Purpose: To identify factors that are significantly associated with patient satisfaction in urology and to assess the extent to which satisfaction ratings might be related to hospital and patient characteristics. Materials and Methods: Data used in this study were obtained from 1040 randomly selected urology patients discharged from nine hospitals who responded to a mailed survey. Bivariate and multivariate techniques were used to reveal relations between patient assessments of received care, hospital and patient characteristics. Results: Bivariate analysis showed a strong association between satisfaction scores and length of stay, provider status, work load of nurses and hospital size, with weaker findings pertaining to type of hospital (teaching versus non-teaching) and patient demographics. The multivariate analysis identified nine variables which are associated with overall satisfaction. Strong factors were treatment outcome, the interpersonal manner of medical practitioners and nurses, as well as hotel aspects like accommodation and quality of food. Variables reflecting information receiving about the undergoing treatment were not found to have a significant influence on patient satisfaction. Conclusion: This study identified variables that are related to satisfaction in a urological setting and delivers information about aspects of the hospital stay that are not perceived as relevant by patients. These findings support healthcare professionals with valuable information to meet needs and preferences of patients in urology.